What do times of crisis reveal about the "total" nature of prisons? Analysing the impacts of the COVID-19 crisis within the Scottish prison system - Maycock, Matthew (Journal of criminology, 2023)
Times of crisis within prison settings either at a system-wide level during times of riots or during pandemics or at more personal levels during time in segregation can be particularly challenging times when the prison can feel more ?total? than other times. Goffman's influential work outlines a particular interpretation of the parameters of the total institution, of which prisons were one manifestation. In the years following its publication, a wide range of research has sought to subvert the notion that prisons are total institutions, suggesting a greater permeability of contemporary prison walls. This article calls for a re-consideration of this dismissal, and a reconnection and critical engagement with Goffman's original parameters within the context of the COVID-19 pandemic and associated lockdown. The response to COVID-19 in prison settings, resulted in may prison jurisdictions rolling back on policies that, to an extent, had subverted prisons looking and feeling ?total?, through the increased ?porosity? of prison wall. Through the analysis of 19 letters received from 8 people in custody in one Scottish prison, there emerges a reframed and reconsidered permeability of prison walls. For the participants in this study, the experiences of the COVID-19 lockdown complicate much of the recent critique of the relevance of the total institution as a theoretical frame to analyse contemporary prisons. Ultimately this paper argues, that through analysing the response to the COVID-19 pandemic, it is possible to observe a more essential and ?total? characteristic of contemporary imprisonment. This has been obscured through decades of penal reform, but the total parameters of prison spaces emerges more clearly during times of crisis.